A Study of the Coupling of FET Temperament Traits with Major Depression - Trofimova, Irina N.; Sulis, William (Frontiers in Psychology, 2016)
Objective: Temperament and mental illness have been linked to the same systems of behavioural regulation. A temperament model, carefully structured to respond to subtle differences within systems of behavior regulation, should exhibit distinct temperament patterns in the presence of mental illness. Previous comparisons of temperament profiles in mental disorders used mostly emotionality-related traits. In contrast, the Functional Ensemble of Temperament (FET) model differentiates not only between emotionality traits, but also between traits related to physical, verbal and mental aspects of behavior and maps 12 functional aspects of behavior to temperament traits as well as to symptoms of mental illnesses. This article reports on the coupling of sex, age and temperament traits with Major Depression using the FET framework. Method: Intake records of 467, ages 17-24, 25-45, 46-65, 66-84 were examined, with temperament assessed by the Structure of Temperament Questionnaire (based on the FET). Results: The presence of Major Depression was associated with changes in mean temperament scores on 9 of the 12 traits. The results were in line with the DSM-5 criteria of fatigue (patients with MD reported a significant decrease in three types of endurance - motor-physical, social-verbal and mental), of psychomotor retardation (a significant decrease in physical and social-verbal tempo) and of worthlessness (as low Self-Confidence). The results also showed that three new symptoms, high Impulsivity, high Neuroticism and diminished Plasticity, should be considered as depressive symptoms in future versions of the DSM. As a significant negative result, no interaction of age or sex (with the exception of the Self-Confidence scale) with MD was found for temperament traits. Conclusions: The value of differentiating between physical, social and mental aspects of behaviour is demonstrated in the differential effects of major depression and gender. The value of differentiating between endurance, dynamical and orientation-related aspects of behaviour is demonstrated in the differential effects of age. The deleterious impact of Major Depression on temperament scores appeared to be similar across all age groups. The appearance of high impulsivity, neuroticism and low plasticity deserve further study as associated factors in future versions of the DSM/ICD.